PTH-150 Giant hiatus hernias in the laparoscopic era. (22nd June 2015) - Camprodon, R; Dighe, S; Wan, A; Reddy, M; Vasilikostas, G
Abstract : Introduction: Laparoscopic repair of giant hiatal hernias (LRGHH) remains a major technical challenge in the successful management of this complex surgical pathology. The aim is to present herein our experience and highlight technical tips in ensuring a safe and efficient approach that improves outcome. Method: A retrospective review of patients undergoing elective LRGHH for symptomatic disease was undertaken between January 2011 and September 2014. Size of hiatal defect, herniated contents, surgical variations were recorded and correlated with clinical outcomes. Results: Sixteen LRGHH surgeries were performed by three consultant surgeons [A=8, B=4 and C=4, respectively]. There were six males and 10 females with a median age of 65 years (range 33–74). There were eleven Type 3 and five Type 4 hernias with hiatal defect ranging from 2.8 to 7 cm. Complete sac excision, meticulous crural dissection and repair and Nissen undoplication were performed in all cases. Collis gastroplasty for shortened oesophagus was fashioned in 4 cases, mesh applied in 1 case and Teflon pledgets in further 3 cases. Eight (50%) patients remained asymptomatic at 6 weeks, five (31%) reported minimal reflux that had settled at 4-month follow up. Complications occurred in 3 patients (18.7%) and included: immediate hernia recurrence with gastric necrosis requiring laparoscopic sleeve gastrectomy, recurrent vomiting that underwent laparoscopic adhesiolysis 18 months post initial procedure and post-operative dysphagia requiring endoscopic dilatation. All 3 patients remained symptom free at 24 months. Conclusion: This report represents the largest reported series in the UK in the modern laparoscopic era. Extensive oesophageal mobilisation to ensure adequate intra-abdominal length and strong crural repair with minimal tension are key to a successful repair. Minimally invasive surgery for such complex major pathology allows perioperative morbidity to remain low with good early outcomes. Disclosure of interest: None Declared. References: Laparoscopic repair of giant paraesophageal hernia: 100 consecutive cases Luketich JD, Raja S, Fernando HC, Campbell W, Christie NA, Buenaventura PO, Weigel TL, Keenan RJ, Schauer PR. Ann Surg. 2000;232(4):608–18 Results of laparoscopic repair of giant paraesophageal hernias: 200 consecutive patients Pierre AF, Luketich JD, Fernando HC, Christie NA, Buenaventura PO, Litle VR, Schauer PR. Ann Thorac Surg. 2002;74 (6):1909–15; discussion 1915–6